Challenges and Barriers in Vocational Learning Assessment: A Case Study of Automotive Engineering Expertise Program in Vocational High Schools - Suhartanta Suhartanta; Nirmala Adhi Yoga Pambayun; Fajrin Sidiq Muzzaffarul Zaman; Yusri bin Kamin (Jurnal Pendidikan Progresif, 2026)
This study aims to analyze the challenges and barriers encountered in vocational learning assessment and to propose a model to strengthen assessment practices based on empirical findings. A qualitative multiple-case study was conducted in one public and one private vocational high school in the Special Region of Yogyakarta, Indonesia, from March to October 2025. Six productive-subject teachers with at least 8 years of teaching experience were purposively selected. Data were collected through in-depth semi-structured interviews and document analysis of lesson plans, teaching modules, assessment instruments, and learning outcome records. We combined document analysis with in-depth interviews (triangulation) to maximize data validity. Thematic analysis was carried out with ATLAS.ti 22 through data familiarization, initial coding, theme generation, theme review, theme definition, and reporting. Trustworthiness was strengthened through source triangulation, member checking, peer debriefing, and cross-case comparison. The study identified multidimensional challenges in the cognitive, psychomotor, and affective domains. Cognitive assessment was constrained by low student literacy engagement, the dominance of multiple-choice tests, limited use of diagnostic assessment, and weak follow-up of item analysis. Psychomotor assessment was constrained by limited facilities, limited teaching time, equipment wear, and uneven opportunities for observing individual performance. These barriers differed between the two schools due to variations in management flexibility, team teaching, procurement, and industry involvement. Affective assessment was constrained by large class sizes, limited observation time, teacher reliance on informal impressions, and the absence of explicit attitude assessment rubrics. The findings indicate the need for a context-sensitive model that strengthens meaningful assessment, continuous diagnostic-formative-summative cycles, resource collaboration, and teacher capacity. The proposed model remains hypothetical and requires further validation and testing of its effectiveness. Keywords: vocational learning assessment, cognitive, psychomotor, affective, case study.